Effect and safety of acupuncture for Hwa-byung, an anger syndrome: a study protocol of a randomized controlled pilot trial - Hye-Yoon Lee; Jung-Eun Kim; Mikyung Kim; Ae-Ran Kim; Hyo-Ju Park; O-Jin Kwon; Jung-Hyo Cho; Sun-Yong Chung; Joo-Hee Kim (Trials, 2018)
Abstract Background Hwa-byung (HB) is an anger syndrome caused by an inadequate release of accumulated anger that leads to somatic and psychiatric symptoms. As HB results from long-term inadequately treated negative emotions, its symptoms are complex, intractable and concomitant with other psychiatric disorders. Therefore, studies aiming to develop effective and safe treatment options for HB are needed. We plan to conduct a pilot study for a future, full-scale, randomized controlled trial (RCT) of an optimal acupuncture procedure using semi-individualized acupuncture points that consider participants’ personal disposition and type of emotional stress. Method/design This randomized, sham-controlled, participant- and assessor-blinded pilot trial aims to determine the study feasibility of acupuncture for HB and to explore its clinical effects and safety. This clinical trial will be conducted with two groups: one treated with real acupuncture and the other with sham acupuncture for 10 sessions over 4 weeks. The experimental group (EG) will receive semi-individualized acupuncture, whereas the control group (CG) will receive sham acupuncture, namely minimal acupuncture on non-acupuncture points. The recruitment, compliance, and completion rate and clinical evaluations, including a Visual Analogue Scale (VAS), the Korean version of the Beck Depression Inventory (BDI), the short form of the Stress Response Inventory (SRI-short form) and the Instrument of the Oriental Medical Evaluation for HB (IOME-HB), will be assessed to evaluate feasibility and possible effects and safety. Four weeks after completing treatment, follow-up assessments will be performed. Discussion As this is a pilot study mainly aiming to investigate trial feasibility, the results of this study will be analyzed descriptively and interpreted for the study purposes. Cohen’s d will be reported to determine the effect of acupuncture for HB and to enable comparisons with other treatment methods. This protocol is significant in that it provides optimal semi-individualized acupuncture treatment. We expect this study to offer information about the feasibility of this treatment and data about the possible effects and safety. Trial registration Clinical Research Information Service (CRIS), Republic of Korea: KCT0001732. Registered on 14 December 2015.